Direct and indirect impact of 10-valent pneumococcal conjugate vaccine introduction on pneumonia hospitalizations and economic burden in all age-groups in Brazil: A time-series analysis. - Ana Lucia Andrade; Eliane T Afonso; Ruth Minamisava; Ana Luiza Bierrenbach; Elier B Cristo; Otaliba L Morais-Neto; Gabriela M Policena; Carla M A S Domingues; Cristiana M Toscano (PLoS ONE)
Background Ten-valent pneumococcal conjugate vaccine (PCV10) was introduced in the National Immunization Program of Brazil in March/2010. Although there are recent reports of PCV10 impact on pneumonia hospitalizations, there is still uncertainty regarding the indirect impact in individuals non-targeted by vaccination. We assessed both direct and indirect effect of PCV10 on pneumonia hospitalizations and the impact on the economic burden of pneumonia hospitalizations. Methods An interrupted time-series analysis was conducted considering monthly rates of pneumonia hospitalizations and comparison groups, in all age-groups, from January/2005-December/2015. We used records of the National Hospitalizations Information System. Observed pneumonia rates in the post-vaccination period (2011–2015) were compared to predicted rates, should PCV10 had not been introduced. Relative percent difference in rates and its 95% confidence interval were estimated. The number of pneumonia hospitalizations averted by vaccination was calculated as the difference between the predicted and observed cumulative number of pneumonia hospitalizations in the post-vaccination period. The impact of PCV10 on economic burden was presented as averted costs of pneumonia hospitalization. Results Significant decrease in rates of pneumonia hospitalization was observed in both children targeted by vaccination (17.4%–26.5%; p<0.01), and in age-groups not targeted by vaccination (11.1%–27.1%, in individuals 10–49 years; p<0.01). In contrast, PCV10 introduction did not alter the increasing trends in pneumonia hospitalization among elderly ≥65 years. A total of 457,564 pneumonia hospitalizations was averted in Brazil for individuals aged <50 years, with a total averted costs of BRL 383.2 million (Int$ 225.2 million, and USD 147 million) for the 5 year period after PCV introduction. Conclusion Vaccination with PCV10 5 years after its introduction in Brazil was associated with a relevant reduction in pneumonia hospitalization in the target age-groups, with an indirect effect in individuals aged 10–49 years, and significant reduction in associated economic burden. The increasing trends in pneumonia hospitalization rates in the elderly is a matter of concern for public health and should be further investigated.